Sosialisasi Program Bantuan Stimulan Perumahan Swadaya (Bsps) Di Nagari Tanjung Barulak Kecamatan Batipuh Kabupaten Tanah Datar Sumatera Barat - Sovia Fardila; Hairani Siregar (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
The concept of a welfare state is closely related to social policy, these social policies are made with the aim of overcoming existing social problems, one of the many social problems faced in several countries, especially developing countries like Indonesia is the problem of poverty, one of the problems Poverty, which until now is still a challenge for the Indonesian state, is the problem of uninhabitable houses. The government has issued various steps to address the problem of uninhabitable housing, one of which is the Self-Help Housing Stimulant Assistance Program (BSPS), the implementation of the BSPS program does not always go easily, especially in Nagari Tanjung Barulak which was implemented in 2019. The problems that have arisen have made This program is less effective in dealing with existing uninhabitable housing problems as an effort to help poverty problems, so it is necessary to increase public knowledge about the Self-Help Housing Stimulant Assistance program.